2023
DOI: 10.3389/fnins.2022.1081124
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory neuronal cells as a promising tool to realize the “druggable genome” approach for drug discovery in neuropsychiatric disorders

Abstract: “Druggable genome” is a novel concept that emphasizes the importance of using the information of genome-wide genetic studies for drug discovery and development. Successful precedents of “druggable genome” have recently emerged for some disorders by combining genomic and gene expression profiles with medical and pharmacological knowledge. One of the key premises for the success is the good access to disease-relevant tissues from “living” patients in which we may observe molecular expression changes in associati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…Several studies have reported a reduced OB volume in these disorders 16,46,[57][58][59][60] , but the sample size of these studies was relatively small. Multiple groups have prepared/enriched primary neuronal cells and stem cells from the OE via nasal biopsy from living subjects [30][31][32][35][36][37][38][39]57,61,62 . Molecular and cellular analyses of these cells from schizophrenia and related disorders have displayed deficits, indicating pathological alternations in the OE in these disorders [30][31][32][35][36][37][38][39]57,61,62 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Several studies have reported a reduced OB volume in these disorders 16,46,[57][58][59][60] , but the sample size of these studies was relatively small. Multiple groups have prepared/enriched primary neuronal cells and stem cells from the OE via nasal biopsy from living subjects [30][31][32][35][36][37][38][39]57,61,62 . Molecular and cellular analyses of these cells from schizophrenia and related disorders have displayed deficits, indicating pathological alternations in the OE in these disorders [30][31][32][35][36][37][38][39]57,61,62 .…”
Section: Discussionmentioning
confidence: 99%
“…Multiple groups have prepared/enriched primary neuronal cells and stem cells from the OE via nasal biopsy from living subjects [30][31][32][35][36][37][38][39]57,61,62 . Molecular and cellular analyses of these cells from schizophrenia and related disorders have displayed deficits, indicating pathological alternations in the OE in these disorders [30][31][32][35][36][37][38][39]57,61,62 . Although changes associated with the olfactory system in patients with schizophrenia and related disorders are prominent and reproducibly reported from many groups 1,3,7,14,16,18,20,30,35,39,46,[57][58][59][60]63 , their mechanistic link is unclear.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…ONCs have several additional advantages. As these are biopsied from living subjects, ONCs allow for studies linking neuronal molecular profiles to clinical manifestations (Jaaro-Peled et al, 2022; Mihaljevic et al, 2022). As the olfactory neural epithelium can regenerate quickly, repeated biopsies are possible.…”
Section: Discussionmentioning
confidence: 99%